Competitiveness of Export-Based Small and Medium Industries (IKM): Case Study of Creative in DKI Jakarta - Karil Maulita; Sri Indah Nikensari; Saparudin Mukhtar (Equity: Jurnal Ekonomi, 2021)
Ministry of Industry assesses that the processing industry is still consistently contributing the most tothe achievement of export value national. There are manufacturing industry sectors that have achieved lowscores on the contribution of export value. Namely the apparel industry, wood industry, and industrialfurniture. There are obstacles and problems for the three industries to increase export value. The problem isthe low competitiveness of the three industries in exporting. This study aims to analyze and see thecondition of the competitiveness of the Small and Medium Creative Industry in the KI Jakarta basedon exports from the supply-side analysis. This research is qualitative research using interview and surveymethods. The samples of this research were Furniture / Furniture IKM, Batik IKM, and Handicraft IKMwhich succeeded in contributing the export contribution value to IKM. The results of this study indicate thatthe conditions of the three creative SMIs in Jakarta have different capabilities and strategies in contributing toexport value. Based on the results of the SWOT and SPACE matrix analysis, a special strategy is needed toincrease competitiveness. Among them, the right strategies are Furniture IKM and Handicraft IKM located inthe quadrant size “aggressive” which indicates that the Furniture IKM in DKI Jakarta is in a very goodposition in using its internal strength. Therefore, the strategies suitable for use by IKM Furniture in DKI Jakartainclude market penetration strategy, market development, product development, backward integration, forwardintegration, horizontal integration, or diversification. Meanwhile, IKM Batik is in the quadrant position“Conservative” which indicates that IKM Batik is in a low or weak competitive position and must improve thecompany's strategic position to have strong competitiveness.